Sustainability of Indonesian Islamic Banking in terms of Corporate Ethical Identity and Corporate Governance - Budi Sukardi; Agung Abdullah; Fuad Dhiya Ul Husaen (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
This study empirically demonstrates efforts to strengthen the performance of identity and corporate governance on the sustainability of Islamic banking in Indonesia, the influence of corporate identity performance on Islamic banking governance in Indonesia, and the influence of the performance of corporate identity and governance on the sustainability of Islamic banking in Indonesia. This is due to the low social function of Islamic banks in Indonesia towards the sustainability of better business, social, and environmental performance. Types of quantitative research with an ex post facto research design. The research population of all Islamic banks in Indonesia included BMI, BSI, BMSI, and BSMI samples. The data were analysed using simple additive weighting techniques by modelling using SEM-PLS techniques. The study's conclusions show that strengthening corporate identity performance and corporate governance towards the sustainability of Islamic banking in Indonesia is carried out with regulations, policies, and Sharia compliance. Corporate identity performance positively and significantly affects Islamic banking governance in Indonesia. A company's management has no effect on the sustainability of Islamic banking in Indonesia. This study provides recommendations from the government as a policy regulator that contributes to the supervision of Islamic banks in Indonesia, especially in the implementation of corporate governance, which includes the ethical performance of companies and the sustainability of Islamic banking in Indonesia by making systematic regulations as a reference for Islamic banks. Islamic banks in Indonesia need to re-reflect on neglected social activities because they prioritise commercial activities too much, thus ignoring social activities which are also at the core of bank activities as intermediary institutions and financial services.